2018
DOI: 10.1684/epd.2018.0996
|View full text |Cite
|
Sign up to set email alerts
|

Sleep‐related hypermotor epilepsy and peri‐ictal hypotension in a patient with syntaxin‐1B mutation

Abstract: STX1B is a gene that encodes syntaxin-1B. STX1B mutations have recently been implicated in fever-associated epilepsy syndromes. However, these have not previously been reported in sleep-related hypermotor epilepsy. A 20-year-old man with a strong family history of epilepsy was investigated in our epilepsy monitoring unit due to uncontrolled epilepsy, compatible with sleep-related hypermotor epilepsy. Electroclinical and polygraphic physiological recordings revealed left frontal epileptiform discharges and prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…STX1B gene mutation may be related to the SHE phenotype and autonomic dysfunction, characterized by peri-ictal hypotension, and testing for this gene should be considered in such patients. 42 In this study, a variant of unknown significance was also detected in the PPT1 gene (encoding palmitoyl protein thioesterase 1), but whether it plays a role in SHE needs further experimental verification. 42 A case report suggests that SHE may also be associated with mutations in the TSC1 gene, which plays a pathogenic role in SHE through the (mTOR) pathway.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…STX1B gene mutation may be related to the SHE phenotype and autonomic dysfunction, characterized by peri-ictal hypotension, and testing for this gene should be considered in such patients. 42 In this study, a variant of unknown significance was also detected in the PPT1 gene (encoding palmitoyl protein thioesterase 1), but whether it plays a role in SHE needs further experimental verification. 42 A case report suggests that SHE may also be associated with mutations in the TSC1 gene, which plays a pathogenic role in SHE through the (mTOR) pathway.…”
mentioning
confidence: 77%
“…42 In this study, a variant of unknown significance was also detected in the PPT1 gene (encoding palmitoyl protein thioesterase 1), but whether it plays a role in SHE needs further experimental verification. 42 A case report suggests that SHE may also be associated with mutations in the TSC1 gene, which plays a pathogenic role in SHE through the (mTOR) pathway. 43 Recent studies in epileptic brain tissues have suggested that defective expression of circadian locomotor output cycles kaput (CLOCK), a transcription factor that regulates the circadian rhythm and mTOR pathway, may be responsible for the predisposition of epileptic seizures during sleep.…”
mentioning
confidence: 77%
“…(2019) for a comprehensive review of the clinical spectrum of STX1B ‐associated epilepsies). At least 26 distinct heterozygous syntaxin‐1B mutations have been identified, including 10 missense mutations, 5 nonsense mutations, 5 frameshift mutations, 1 complex insertion‐deletion, two splice site variants, and 3 cases of STX1B whole gene deletion (Krenn et al., 2020; Peres et al., 2018; Schubert et al., 2014; Vlaskamp et al., 2016; Wolking et al., 2019). It is important to note that seizure type varies even within families harbouring the same mutation and incomplete penetrance was observed in two large families (Schubert et al., 2014; Wolking et al., 2019).…”
Section: Syntaxin‐1mentioning
confidence: 99%
“…Most of these mutations were predicted to cause haploinsufficiency of STX1B, resulting in early termination of the protein. Sixty-two individuals have been described so far and the mainly reported phenotype was epilepsy (Table 2) (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Wolking et al (23) divides STX1Bassociated epileptic phenotypes in four different groups: (1) benign epilepsy syndrome with febrile and afebrile seizures corresponding to "genetic epilepsies with febrile seizures plus, " (2) "genetic generalized epilepsy" phenotype, (3) "developmental and epileptic encephalopathy" syndrome with refractory seizures and moderate to severe developmental deficits, and (4) focal epilepsy phenotype.…”
Section: Proteins Of the Main Snare Complex Stx1bmentioning
confidence: 99%